Experiences of individuals with visual impairments in integrated physical education: A retrospective study - Haegele, Justin A; Zhu, Xihe (Research quarterly for exercise and sport, 2017)
Purpose: The purpose of this retrospective study was to examine the experiences of adults with visual impairments during school-based integrated physical education (PE). Method: An interpretative phenomenological analysis (IPA) research approach was used and 16 adults (ages 21-48 years; 10 women, 6 men) with visual impairments acted as participants for this study. The primary sources of data were semistructured audiotaped telephone interviews and reflective field notes, which were recorded during and immediately following each interview. Thematic development was undertaken utilizing a 3-step analytical process guided by IPA. Results: Based on the data analysis, 3 interrelated themes emerged from the participant transcripts: (a) feelings about "being put to the side," frustration and inadequacy; (b) "She is blind, she can't do it," debilitating feelings from physical educators' attitudes; and (c) "not self-esteem raising," feelings about peer interactions. The 1st theme described the participants' experiences and ascribed meaning to exclusionary practices. The 2nd theme described the participants' frustration over being treated differently by their PE teachers because of their visual impairments. Lastly, "not self-esteem raising," feelings about peer interactions demonstrated how participants felt about issues regarding challenging social situations with peers in PE. Conclusions: Utilizing an IPA approach, the researchers uncovered 3 interrelated themes that depicted central feelings, experiences, and reflections, which informed the meaning of the participants' PE experiences. The emerged themes provide unique insight into the embodied experiences of those with visual impairments in PE and fill a previous gap in the extant literature. (Autor).